Ultrastructure of spermatogonia and primary spermatocytes of C57BL6J mice - Martins, MRFB; Silva, JRCP (Blackwell Wissenschafts Verlag Gmbh, 2001)
The three types of spermatogonia were confirmed. Type A spermatogonia have a large nucleus and loose chromatin and are poor in endoplasmic reticulum. The second type, B spermatogonia, have rounded and smaller nuclei filled with more electron-dense nucleoplasmic material. The endoplasmic reticulum has the aspect of round or elongated cisterns that are free in the cytoplasm or close to the basement membrane. In contrast, intermediate spermatogonia present chromatin material with intermediate condensation compared with the two previous cell types. Primary spermatocytes are characterized by the presence of intercellular bridges and a synaptonemal complex. In the late pachytene stages, the synaptonemal complex was found to be enveloped by chromatin material.